Pengaruh Foreign Direct Investment, Harga Minyak Dunia, Suku Bunga dan Nilai Tukar terhadap Return Indeks Harga Saham Gabungan Periode 2018-2022 - Indah Ameilia Shedo; Gatot Nazir Ahmad; Destria Kurnianti (Journal of Business Application, 2023)
This study aims to test and analyze the effect of Foreign Direct Investment (FDI), World Oil Prices, Interest Rates, and Exchange Rates on the Return of the Composite Stock Price Index (JCI) for the 2018-2022 Period. The control variables used in this study are Covid-19 dummy and stock trading volume. The sample of this study is companies that consistently trade on the Indonesia Stock Exchange for the period 2018-2022 (60 observations). This study uses time series data. The theory used in this research is signal theory. The research data were tested using multiple linear regression tests, classical assumption tests, coefficient of determination tests, and t hypothesis tests. The test results show that world oil prices and interest rates have a significant positive effect on JCI returns, while the exchange rate and Covid-19 dummy have a significant negative effect on JCI returns. Foreign Direct Investment (FDI) and stock trading volume have no significant effect on JCI returns. Keywords: foreign direct investment (fdi), crude oil price , exchange rate ,jci return, , interest rate.